Effectiveness of Lactation Management on Breastfeeding Self-Efficacy: A Quasi-Experimental Study - Siska Ningtyas Prabasari (Gaster, 2026)
Introduction: Lactation management includes education, problem-solving, and support to ensure successful breastfeeding. A key factor influencing this success is maternal self-efficacy, or a mother’s confidence in her ability to breastfeed. Higher self-efficacy helps mothers overcome breastfeeding challenges and maintain breastfeeding longer. Objective: This study aims to evaluate the effectiveness of lactation management on breastfeeding self-efficacy among breastfeeding mothers. Method: A quasi-experimental pretest–posttest control group design was used with 30 breastfeeding mothers of infants aged 0–6 months selected through purposive sampling. The intervention group received lactation management education delivered in three structured sessions, while the control group received no intervention. Breastfeeding self-efficacy was assessed using the BSES-SF before and after the intervention. Result: The intervention group showed a significant increase in self-efficacy scores (p < 0.001), whereas the control group showed no significant change (p > 0.05). There was also a significant difference in posttest scores between the two groups (p < 0.001). Conclusion: Education and practice based lactation management proved effective in strengthening mothers’ confidence in breastfeeding. Integrating this intervention into primary health services is recommended to support the success of exclusive breastfeeding and to aid in stunting prevention.